KETIDAKJUJURAN AKADEMIK PADA SAAT UNBK TAHUN 2017 - Herdian Herdian (Jurnal Psikologi Jambi, 2018)
INTRODUCTION The use of komputer in the national exam is a new breakthrough in the national examination sistem in Indonesia. The use of komputers is expected to minimize the practice of dishonesty in National Examination work that had sounded "leaked" in previous years. Presented by Muhadjir Effendy as Minister of Education and Culture of Indonesia related targets of enactment of UNBK is to prevent the possibility of fraudulent practices, both sporadic and massive. METHOD This study uses a quantitative approach descriptive survey method to uncover the dishonest behavior when doing UNBK Year 2017. The subjects of this study are 74 students who have passed on the level of high school or level and do dishonesty at the time of UNBK Year 2017. Sampling technique in this study using incidental sampling. The method of analysis used to answer the purpose of research using descriptive analysis techniques. RESULT Based on the results of this study, dishonesty when doing UNBK in 2017 can not be said completely from academic dishonesty despite the execution of komputer-based exams. The results mention forms of academic dishonesty including asking for answers, cheating friends secretly, searching from the internet, providing answers and carrying notes / cheat sheet. The academic dishonesty at UNBK in 2017 was not the first time performed by students, as evidenced by the beginning of academic dishonesty at the elementary school. Academic dishonesty is also taught by the school. CONCLUSION AND RECOMMENDATION Eradicating academic dishonesty is not only influenced by how to do the problem, one with the komputer. For the government to be able to evaluate the sistem especially komputer-based workmanship. To the school to be an example that gives an example so that dishonest behavior can be minimized, especially in the execution of the exam.